HYDROGRAPHIC NETWORK EXTRACTION AND WATERSHEDS DELIMITATION SOFTWARE OF THE SOUTH ORAN NORTH WESTERN ALGERIA - Ayache, A.; Bennia, A. R.; Lebid, S.; Hellal, B.; Maacho, A. (University of Eloued جامعة الوادي, 2018)
The development of space technology has allowed a better understanding and effective use of water resources through the use of Digital Terrain Models or DTM. Mapping the river system from DTM has two objectives, namely identifying first topography descriptors like hills, ridges and valleys of watersheds and second hydrological parameters to map areas of runoff recovery for a more efficient development and also a better representation of the actual land occupation. Our work is part of a methodological approach to satellite imagery processing and mapping of topographic and hydrographic parameters of watersheds. Thus, from DTM one was able to extract the full river system of the region. The results show a remarkable evolution of human activities and especially in areas of high water recovery capacity.
Articale in Journal of fundamental and Applied Sciences Vol. 10, N. 01
Keywords: remote sensing, DTM, network hydrology, geographic, steppe, west of Algeria.